Determination of lipase and amylase activities from wood decay fungi - Lai, Shu Ying (2015)
Fungal enzymes have long history of usage in various industries. Lipase and amylase are two of the most commercialized enzymes to date. Wood decay fungi are promising source of amylase and lipase. A number of fungi had been isolated from decayed tree bark. Isolates were screened with minimal media supplemented with specific carbon source, starch and tween 80 respectively.. Starch was used for screening of amylase producing fungi while tween 80 was used for screening of lipase producing fungi. Two amylase producing fungi identified to be Aspergillus sp. and Fusarium sp. were isolated. For lipase producing fungi, Cladosporium sp. and Aspergilus sp. were isolated. Fungal isolates were analyzed for its amylase and lipase activity. Fusarium sp. has highest amylase activity of 53.69U/ml while Cladosporium sp. reported highest lipase activity of 503.02 U/ml. Growth rate analysis was done to further verify the amylolytic and lypolytic capability of isolates.